2010
DOI: 10.1002/tax.592002
|View full text |Cite
|
Sign up to set email alerts
|

The oaks of western Eurasia: Traditional classifications and evidence from two nuclear markers

Abstract: Phylogenetic relationships among species of Quercus (oaks) from western Eurasia including the western part of the Himalayas are examined for the first time. Based on ITS and 5S–IGS data three major infrageneric groups are recognized for western Eurasia: the cerroid, iliciod, and roburoid oaks. While individuals of the cerroid and ilicoid groups cluster according to their species, particularly in the 5S–IGS analyses, individuals of species of roburoid oaks do not cluster with exception of Quercus pontica. The C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
212
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(239 citation statements)
references
References 45 publications
(81 reference statements)
21
212
0
4
Order By: Relevance
“…We hypothesize that some of these divergences can be correlated with the different number of rDNA loci present in this group, where different FISH patterns are found: either the same, as in all species of subgenus Quercus and other Cyclobalanopsis species (Chokchaichamnankit et al 2008), or different with a high number of paralogous sites. Moreover, Denk and Grimm (2010), based on ITS and 5S-IGS data, concluded that the Cyclobalanopsis group shares a common ancestor with the Cerris and Ilex groups, and at the same time is closer to other Fagaceae than to the remainder of species of the Quercus genus. Interestingly, these phylogenetic patterns indicate that the Cyclobalanopsis group was isolated, and possibly radiated soon after the initial divergence, separating the two major clades within oaks.…”
Section: Discussionmentioning
confidence: 97%
“…We hypothesize that some of these divergences can be correlated with the different number of rDNA loci present in this group, where different FISH patterns are found: either the same, as in all species of subgenus Quercus and other Cyclobalanopsis species (Chokchaichamnankit et al 2008), or different with a high number of paralogous sites. Moreover, Denk and Grimm (2010), based on ITS and 5S-IGS data, concluded that the Cyclobalanopsis group shares a common ancestor with the Cerris and Ilex groups, and at the same time is closer to other Fagaceae than to the remainder of species of the Quercus genus. Interestingly, these phylogenetic patterns indicate that the Cyclobalanopsis group was isolated, and possibly radiated soon after the initial divergence, separating the two major clades within oaks.…”
Section: Discussionmentioning
confidence: 97%
“…The Fagaceae species are considered as keystone species in forest ecosystem and are important drivers of terrestrial biodiversity. Quercus L., the largest genus in Fagaceae family, comprises ∼400 species; most of the diversity of the genus lies in Central America and Southeast Asia (Denk and Grimm 2010). However, till now, extensive genetic and genomic studies are conducted mainly on less species-rich European oaks (e.g., Kremer and Petit 1993;Kremer et al 2010;Plomion et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…covering three of the five or six major intrageneric lineages ( Q. faginea, Q. pyrenaica, Q. rubra and Q. suber ) [17], [19], [55], in two Castanea spp. ( C. sativa and C. mollissima ) from different geographic origins, and in Fagus sylvatica .…”
Section: Resultsmentioning
confidence: 99%
“…More gene types than the number of 35S rDNA loci suggest that different variants occur in the same locus indicating an insufficient homogenization of the IGS. Moreover, in Q. petraea and Q. robur three divergent rDNA clusters have been isolated [30], and intra-individual variability was found in ITS and 5S-IGS [17]. Differences in the number of length variants have been correlated with several traits in wild and cultivated plants and seem to have ecological significance that can respond to selection pressure (revision in [2]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation